Synergestic effect of gallic acid lipid nanoparticles to improve the physiochemical property and cellular uptake against MDA MB 231 Cancer cell line: Apoptosis, signaling pathway and cytotoxicity - Sandhiya .V; Priyanka Sinha; T.Sathish Kumar; R. Siva kumar; Swetha B; Deepika A; Sona Jain P; Theresa Evangilin P (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Introduction: Gallic acid (GA), a phenolic molecule that occurs naturally, has been shown to have anti-tumor properties for a number of cancer types. The effect of GA on breast tumor cells MDA-MB-231 Triple Negative was examine in the current study.Methods: Techniques were utilised for cell cycle analysis, GSH concentration, Annexin V assay, light and fluorescence microscopy, restriction of cell growth (MTT assay), preparation, characterisation, and measurement of the mitochondrial membrane potential.Results: It was shown that the produced GANP significantly reduced the ability of MDAMB-231 cells to multiply. Moreover, this might result in glutathione depletion, an increase in ROS levels, and cytotoxic activity in MDA-MB-231 cells. Analysis using flow cytometry revealed so as to the GANP enhanced the inhabitants of sub-G1 cells. Also, the Annexin V/PI test and fluorescence labelling both established so as to the addition of GA dramatically increased the amount of apoptotic cells. Therefore, research of the oxidative damage-related sickness revealed that the amalgamation of GA greatly decrease oxidative damage in healthy cells while increasing glutathione levels and lowering lipid peroxidase levels in MDA-MB-231 cellsConclusion: These consequences propose that GA as GANP may have potential as a chemopreventive treatment for triple negative breast cancer.